Estimation of cardiac flow in children by means of imaging gated pulse Doppler - NOWICKI, A.; SECOMSKI, W.; PLESKOT, M. (Archives of Acoustics, 1984)
Imaging pulse cardiac Doppler was used to investigate congenital heart conditions in children. Preliminary investigations were carried out in a group of 15 healthy children and in 23 children with congenital heart diseases. The recordings in normal children and in children with ventricular septal defect (VSD), atrial septal defect (ASD), patent ductus arteriosus (PDA) and with coarctation of aorta (CoA) will be shown.